Analysis and Modeling of the Variations of Root Branching Density Within Individual Plants and Among Species - Pagès, Loïc (Frontiers in Plant Science, 2019)
Branching density (or the reciprocal: inter-branch distance) is an important trait which contributes to defining the number of roots in individual plants. The environmental and local variations in inter-branch distance have often been stressed, and simulations models have been put forward in order to take them into account within the dynamics of root system architecture (RSA). However, little is known about the interspecific and intra-plant variations of inter-branch distance. In this paper, we present an analysis which draws on 40 samples of plants belonging to 36 species collected in homogeneous soils, in order to address how the variations in inter-branch distance are structured within individual plants, and how this structure varies from one species to another. Using measurements of inter-branch distance on various roots of the same species and our knowledge of the branching process, we defined a simple and generic model dedicated to the simulation of the observed variations. This model distinguishes between two sub-processes: (i) the longitudinal location of potential branching sites and (ii) the effective emergence of lateral roots at these sites. Thus, it represents the variations in distance between the potential sites (with 2 parameters), and the probability of emergence of a lateral root at each site (1 parameter). We show the ability of this model to account for the main variations in inter-branch distances with a limited number of parameters, and we estimated them for the different species. These parameters can be considered as promising traits in order to characterize -in a comprehensive and simple way- the genetic and environmental variations in the whole branching process at plant level. Based on the results, we make recommendations for carrying out comparable measurements of the branching density in developed plants. Moreover, we suggest the integration of this new model as a module in future RSA simulators, in order to improve their capacity to account for this important and highly variable characteristic of plant species.